PENERAPAN TEKNIK GRAVITASI DALAM PENGAWETAN BAMBU UNTUK MENINGKATKAN KUALITAS BAMBU PASCA PENEBANGAN - Simpen, IN.; Negara, IM. Sutha; Widihati, I.A.G. (Buletin Udayana Mengabdi; Vol 11 No 1 (2012): Volume 11 No.1 – April 2012, 2012)
The Community Service was held to produce bamboo preserved by borax solution through using gravity technique toward the bamboo crafting raw material in Desa Pengotan, Bangli, therefore people are free from beetle attack. The preserved bamboo will improve quality. The activity was realized by several steps, namely surveys to fix the activity schedule, prepare materials, perform the demonstration plot, apply test, execute, and discuss. From the training in technological application, tuition, and evaluation conducted, the people is very enthusiastic in attending execution of this activity. They considered because the applied technology and yielded product are something new. Besides, the people do not find difficulties in accepting and executing this technology so that they can yield raw material bamboo which have been easily preserved.